2020
DOI: 10.1128/mbio.03186-19
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Metabolomic Signatures in Colorectal Adenoma Patients Are Associated with Gut Microbiota and Early Events of Colorectal Cancer Pathogenesis

Abstract: Colorectal adenomas are precancerous lesions of colorectal cancer (CRC) that offer a means of viewing the events key to early CRC development. A number of studies have investigated the changes and roles of gut microbiota in adenoma and carcinoma development, highlighting its impact on carcinogenesis. However, there has been less of a focus on the gut metabolome, which mediates interactions between the host and gut microbes. Here, we investigated metabolomic profiles of stool samples from patients with advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 79 publications
3
126
1
Order By: Relevance
“…Insufficient human studies have evaluated the metabolome and microbiota in relation to adenomas. Findings from a recent study suggest that there is a correlation between bacterial dysbiosis, the metabolome, and colorectal adenomas [ 92 ]. More studies are required to fully explore the correlation between microbiota, metabolome, and ACP.…”
Section: Pro and Prebiotic In Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient human studies have evaluated the metabolome and microbiota in relation to adenomas. Findings from a recent study suggest that there is a correlation between bacterial dysbiosis, the metabolome, and colorectal adenomas [ 92 ]. More studies are required to fully explore the correlation between microbiota, metabolome, and ACP.…”
Section: Pro and Prebiotic In Human Healthmentioning
confidence: 99%
“…In fact, the microbiota influences the host through their metabolites. Kim and his collaborators found that, in patients with ACP, a high concentration of bioactive lipids, including polyunsaturated fatty acids, sphingolipids, and secondary bile acids, existed [ 92 ]. All these compounds are produced by the bacteria species that are dominant (in number) in patients with adenomas and CRC.…”
Section: Gut Microbiota and Their Metabolites In Adenomatous Colonmentioning
confidence: 99%
“…2020 (Kim et al, 2020) Non-nucleatum Fusobacteria common in southern Chinese populations are associated with colorectal cancer:…”
Section: Descriptionmentioning
confidence: 99%
“…Colorectal adenoma (CRA) is defined as non-cancerous lesion of the large intestinal epithelium. It is commonly acknowledged that CRA is a precancerous condition and may progress to colorectal cancer (CRC) that is a common reason of cancer death worldwide, with the unknown etiology and pathogenesis (Fearon, 2010;Kim et al, 2020). In spite of certain progress recently, the understanding of underlying biomolecules of CRA is rather rudimentary and the process of screening these biomolecules is still continuing.…”
Section: Introductionmentioning
confidence: 99%